KOMUNIKASI PEMASARAN CLOTHING YESZY MFG - Siswanta, Wahyu Mardiyanto, Maya Sekar Wangi & (Transformasi, 2017)
This research was about communication marketing in an enterprise clothes called YESZY MFG.The purpose of this research is to explain and described of marketing communication clothingYESZY MFG in pulling the community to use products. In this research using the teory ofHermawan and the teory Kotler. A kind of research methodelogy used is research descriptionqualitative. The results of the study data shows that in communication marketing online YESZYMFG use social media including facebook & instagram as a means of promotion andcommunication marketing offline YESZY MFG is by means introduce products throughendorsment, sponsorship, flyering, submit clothes in retail store, follow the exhibition clothing,then marketing carried out through YESZY MFG employees.Key words: communication marketing online, communication marketing offline, YESZY MFG.